Effectiveness of using e-government platform "Absher" as a tool for noncommunicable diseases survey in Saudi Arabia 2019-2020: A cross-sectional study - Mohammed Alluhidan; Mohammed Alluhidan; Reem F. Alsukait; Taghred Alghaith; Rana Saber; Adwa Alamri; Saleh Al-Muhsen; Fahad Alhowaitan; Abdulmohsen Alqarni; Christopher H. Herbst; Nahar Alazemi; Ahmad S. Hersi (Frontiers Media S.A., 2022)
BackgroundE-government platforms provide an opportunity to use a novel data source for population health surveillance (also known as e-health). Absher is a Saudi e-government platform with 23 million authenticated users, including residents and citizens in Saudi Arabia. All Absher users were invited to participate in a web-based survey to estimate the prevalence of noncommunicable diseases and their risk factors in Saudi Arabia.ObjectiveTo assess the potential of using an e-government platform (Absher) to administer web-based health surveys.MethodsA cross-sectional, web-based health survey was administered to Absher users between April 2019 and March 2020. The survey instrument included eight items and took <5 min to complete. The respondents' data were compared to Saudi Arabia's 2016 census. Descriptive summary statistics of the prevalence of major noncommuncable diseases are presented and compared to population-based prevalence data from Saudi Arabia's World Health Survey (WHS) 2019. All analysis was conducted using Stata 13.0.ResultsOverall, the Absher health survey had a 24.6% response rate, with most respondents being male (84%), Saudi (67%), and between 30 and 44 years of age (49%). Overall, the prevalence of noncommunicable diseases and risk factors among respondents was high for overweight (35%) and obesity (30%) and low for asthma (6%). The prevalence of diabetes, dyslipidemia, and hypertension was between 15 and 17% on average, and 26.5% were smokers. In comparison to population-based World Health Survey estimates, the Absher survey overestimated obesity, diabetes, dyslipidemia, hypertension, and smoking rates, and underestimated overweight, whereas asthma prevalence was similar for Absher and the WHS.ConclusionsWith improvements in the study design, the use of e-government platforms can provide a useful and potentially low-cost data source for public health research.